Increased PPARD Expression May Play a Protective Role in Human Lung Adenocarcinoma and Squamous Cell Carcinoma - Yong Zhu; Yedong Mi; Zhonghua Qin; Xuewei Jiang; Yibo Shan; Kamil Kural; Guiping Yu (PPAR Research)
Peroxisome proliferator-activated receptor-δ, encoded by gene PPARD, is overexpressed in a majority of human lung cancer subtypes, but its role in the tumor progression remains poorly understood. We have analyzed the expression of PPARD in lung adenocarcinoma (LA) and squamous cell carcinoma (LSCC) datasets. The potential roles of PPARD in the pathological development of LA and LSCC were explored through literature-based pathway analysis and pathway enrichment analysis. In all LA datasets (N=11) and in seven out of nine LSCC studies, the levels of PPARD were increased as compared to control tissues (log-fold changes were 0.37±0.20 and 0.10±0.37 for LA and LSCC, respectively). On average, the expression levels of PPARD in LA were higher than those in LSCC (p=0.036). Pathway analysis showed that the overexpression of PPARD might play both positive and negative roles in the development of both LA and LSCC. Specifically, PPARD inhibits seven LSCC promoters and seven LA promoters and activates one LSCC inhibitor and another LA inhibitor. However, PPARD also activates six and one promoters of LA and LSCC, respectively, which would facilitate the development of LA/LSCC. Our results suggested a mixed role of PPARD in LA/LSCC, which may add new insights into the understanding of the PPARD-lung cancer relationship.